Which equation represents the transformation formed by horizontally stretching the graph of f(x) = √x by a factor of 4 and then vertically shifting the graph 2 units down?
Responses

A. [tex]g(x)=\sqrt{\frac{1}{4} x[/tex][tex]-2[/tex]

B. [tex]g(x) =4\sqrt{x}[/tex][tex]-2[/tex]

C. [tex]g(x)=\sqrt{4x}[/tex][tex]-2[/tex]

D. [tex]g(x)=\sqrt{4x-2}[/tex]

Which equation represents the transformation formed by horizontally stretching the graph of fx x by a factor of 4 and then vertically shifting the graph 2 units class=

Respuesta :

Answer:

[tex]\textsf{A.} \quad g(x)=\sqrt{4x}-2[/tex]

Step-by-step explanation:

Transformations

For a > 0

[tex]f(x)+a \implies f(x) \: \textsf{translated $a$ units up}[/tex]

[tex]f(x)-a \implies f(x) \: \textsf{translated $a$ units down}[/tex]

[tex]a\:f(x) \implies f(x) \: \textsf{stretched parallel to the $y$-axis (vertically) by a factor of $a$}[/tex]

[tex]f(ax) \implies f(x) \: \textsf{stretched parallel to the $x$-axis (horizontally) by a factor of $\dfrac{1}{a}$}[/tex]

Given parent function:

[tex]f(x) = \sqrt{x}[/tex]

1.  Horizontal stretch by a factor of 4:

f(4x) is a horizontal stretch by a factor of 1/4.

So f(1/4x) is a horizontal stretch by a factor of 4.

[tex]f\left(\frac{1}{4}x\right)\implies g(x)=\sqrt{\frac{1}{4}x}[/tex]

2. Vertical shift by 2 units down:

[tex]f\left(\frac{1}{4}x\right)-2\implies g(x)=\sqrt{\frac{1}{4}x}-2[/tex]

ACCESS MORE